Changes in nationwide use of preoperative radiotherapy for rectal cancer after revision of the national colorectal cancer guideline. Issue 7 (July 2017) - Gietelink, L.; Wouters, M.W.J.M.; Marijnen, C.A.M.; van Groningen, J.; van Leersum, N.; Beets-Tan, R.G.H.; Tollenaar, R.A.E.M.; Tanis, P.J.; ,
Abstract: Background: The rate of preoperative radiotherapy (RT) for rectal cancer in the Netherlands has been the highest among European countries. Revision of the national guideline on colorectal cancer, officially published in 2014, specifically focussed on the indication for RT and MRI criteria to evaluate mesorectal lymph nodes. The objective of this study was to evaluate implementation of the revised guideline using a national audit. Methods: Data of the Dutch Surgical Colorectal Audit (DSCA) between 2009 and 2014 were used to evaluate RT use and RT regimen for relevant subgroups of cM0 rectal cancer patients, as well as accuracy of pre-operative MRI. Results: 14, 018 patients were included for analysis. Overall RT use in cT1-4N0-2M0 stage ranged from 81.4% to 84.2% between 2009 and 2013, and decreased to 64.4% in 2014. The absolute decrease in RT use from 2013 to 2014 for cT1N0, cT2N0 and cT3N0 stage was 32.8%, 43.5% and 31.6%, respectively. Short course RT with delayed surgery was used as an alternative to chemoradiotherapy up to 2013 in 30.6% of patients over 80 years, and in 12.1% of patients with an ASA score >2; these percentages increased to 45.8% and 19.9% in 2014, respectively. Specificity of MRI for N-stage decreased from 82.9% in 2009 to 62.9% in 2013, with an increase to 73.2% in 2014. Conclusion: The revised national guideline on colorectal cancer was rapidly implemented in the Netherlands with a substantial decrease in RT use for low risk resectable rectal cancer, and increased specificity of MRI for N-staging.